Pengembangan Aplikasi Perangkat Bergerak Rekomendasi Co-Working Space di Kota Malang berbasis Android - Stefanus Dany Supryatna Sinaga; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
One of the problems experienced by entrepreneurs is the difficulty of making decisions in finding a co-working space that is in accordance with the wishes of the entrepreneur. This problem was obtained based on the results of a survey conducted on five entrepreneurs in the city of Malang. These problems include high rental rates, long distances to locations, less comfort levels, and other problems. Therefore, this research was carried out with the aim of developing a mobile application for recommended co-working space in Malang City based on Android called CoSpace. The CoSpace application was developed using the SDLC waterfall method, Android OS, and Firebase. This research is divided into four steps, namely needs analysis, design, implementation, and testing. Requirements analysis resulted in twelve functional requirements of users and admins and two non-functional requirements. The design stage produces activity diagrams, sequence diagrams, class diagrams, algorithm designs, and interface designs. The implementation phase results in the implementation of program code and interfaces. Validation testing gets 100% valid results. Testing the usability effectiveness of users and admins gets 100% successful results. User and admin usability efficiency tests get 0.001501 and 0.001741 tasks/second. The results of the usability satisfaction (SUS) test are 90.625 (best imaginable). The results of this study can make it easier for entrepreneurs in Malang City to choose a co-working space that suits user needs.